Evaluating Micro and Macro Effects of Regional Development Policies: The Case of the Northeast Regional Fund (FNE) in Brazil, 2000-2006 - Guilherme Resende (European Regional Science Association (ERSA), 2010)
The goal of this paper is to carry out two outcome evaluations of the northeast regional fund (FNE) in Brazil. With this aim, the paper assembles two types of outcome evaluation often implemented separately in the evaluation literature. The results of the micro- and macro-evaluations show that although there is a positive and statistically significant impact of the FNE industrial loans on job creation at the (micro) firm level, this impact is still too limited to have any significant effect on GDP per capita growth at the municipal (macro) level and thus reduce the regional inequalities in Brazil.
Keywords: C52; O20; R58; 330; Evaluation; Regional Development Policy; Regional Inequality; FNE; Brazil